Matching Boundary Conditions for Scalar Waves in Body-Centered-Cubic Lattices (Advances in Applied Mathematics and Mechanics, 2013)
Matching boundary conditions (MBC's) are proposed to treat scalarwaves in the body-centered-cubic lattices. By matching thedispersion relation, we construct MBC's for normal incidence andincidence with an angle alpha. Multiplication of MBC operatorsthen leads to multi-directional absorbing boundary conditions. Theeffectiveness is illustrated by the reflection coefficient analysisand wave packet tests. In particular, the designed M1M1 treats thescalar waves in a satisfactory manner.